2010
DOI: 10.1073/pnas.1008392107
|View full text |Cite
|
Sign up to set email alerts
|

Hydration-controlled bacterial motility and dispersal on surfaces

Abstract: Flagellar motility, a mode of active motion shared by many prokaryotic species, is recognized as a key mechanism enabling population dispersal and resource acquisition in microbial communities living in marine, freshwater, and other liquid-replete habitats. By contrast, its role in variably hydrated habitats, where water dynamics result in fragmented aquatic habitats connected by micrometric films, is debated. Here, we quantify the spatial dynamics of Pseudomonas putida KT2440 and its nonflagellated isogenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
244
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 181 publications
(251 citation statements)
references
References 34 publications
7
244
0
Order By: Relevance
“…For given geometry and cell size, the results depicted in Figure 5 show that cell flagellated velocity was relatively constant under saturated condition, and following air entry, the velocity gradually decreased with matric potential until it reached a critical value where capillary forces pin bacterial cells behind air-water interfaces rendering cells nonmotile [Dechesne et al, 2010;Wang and Or, 2010]. The results indicate that cell velocity never achieves to cell velocity in bulk solution due to cell-wall hydrodynamic interactions (see equation (6)).…”
Section: Bacterial Dispersal Characteristics From Individual To Populmentioning
confidence: 80%
See 2 more Smart Citations
“…For given geometry and cell size, the results depicted in Figure 5 show that cell flagellated velocity was relatively constant under saturated condition, and following air entry, the velocity gradually decreased with matric potential until it reached a critical value where capillary forces pin bacterial cells behind air-water interfaces rendering cells nonmotile [Dechesne et al, 2010;Wang and Or, 2010]. The results indicate that cell velocity never achieves to cell velocity in bulk solution due to cell-wall hydrodynamic interactions (see equation (6)).…”
Section: Bacterial Dispersal Characteristics From Individual To Populmentioning
confidence: 80%
“…However, in unsaturated porous media, heterogeneous geometry and hydration conditions restrict the motility of bacteria to a thin aqueous film due to the cell-wall viscous drag and capillary pinning forces [Dechesne et al, 2010;Wang and Or, 2010]. In the pore network model, we consider each corner of triangular-shaped bonds as a separate pathway for bacterial motion with own effective water film thickness, dðuÞ.…”
Section: Bacterial Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hydration status and pore-space characteristics are critical factors shaping nutrient fields and bacterial motility, and are thus key to understanding bacterial interactions in soil and other porous media such as dry food products (Barton and Ford, 1997;Dens and Van Impe, 2000;Wilson et al, 2002;Chang and Halverson, 2003;Or et al, 2007;Chen and Jin, 2011). Although motility has long been argued as a key factor for survival in heterogeneous environments and for biodiversity maintenance (Fenchel, 2002;Reichenbach et al, 2007;Vos and Velicer, 2008), it is only recently that crucial processes regulating bacterial motility within liquid films forming on partially hydrated rough surfaces have been quantified (Dechesne et al, 2010;Wang and Or, 2010). These studies have shown that surface roughness and aqueous-phase configuration impose capillary and hydrodynamic constraints limiting bacterial motility, and defined a surprisingly narrow range of hydration conditions where motility could confer ecological advantage on rough surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…We employed a hybrid model that couples individual-based description of cell growth, motion and interactions within a nutrient field described by a (continuum-based) reaction À diffusion model (Kreft et al, 1998;Dechesne et al, 2010). The model resolves spatial and temporal nutrient diffusion fields subjected to prescribed boundary conditions, heterogeneity and local nutrient interception by individual cells.…”
Section: Introductionmentioning
confidence: 99%